2003
DOI: 10.1242/jcs.00249
|View full text |Cite
|
Sign up to set email alerts
|

Sexy splicing: regulatory interplays governing sex determination fromDrosophilato mammals

Abstract: A remarkable array of strategies is used to produce sexual differentiation in different species. Complex gene hierarchies govern sex determination pathways, as exemplified by the classic D. melanogaster paradigm,where an interplay of transcriptional, splicing and translational mechanisms operate. Molecular studies support the hypothesis that genetic sex determination pathways evolved in reverse order, from downstream to upstream genes, in the cascade. The recent identification of a role for the key regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Analysis of SREs affected by the exonic editing revealed that the most common abolished splicing regulatory element (SRE) is 5 ′ -AAGAA-3 ′ (47 times out of 267), which is recognized by TRA2A and TRA2B (transformer 2α and transformer 2β homolog, respectively), known activators of AS, which account for sex determination in Drosophila (Lalli et al 2003). The most common newly formed SRE is 5 ′ -GGGA-3 ′ (43 new appearances out of 317), a motif recognized by HNRNPF (regulators of splicing that play a role in splice site selection) (Martinez-Contreras et al 2006).…”
Section: Collection Of Editing Sitesmentioning
confidence: 99%
“…Analysis of SREs affected by the exonic editing revealed that the most common abolished splicing regulatory element (SRE) is 5 ′ -AAGAA-3 ′ (47 times out of 267), which is recognized by TRA2A and TRA2B (transformer 2α and transformer 2β homolog, respectively), known activators of AS, which account for sex determination in Drosophila (Lalli et al 2003). The most common newly formed SRE is 5 ′ -GGGA-3 ′ (43 new appearances out of 317), a motif recognized by HNRNPF (regulators of splicing that play a role in splice site selection) (Martinez-Contreras et al 2006).…”
Section: Collection Of Editing Sitesmentioning
confidence: 99%
“…For detailed information on sex determination in D. melanogaster, the interested reader is referred to other reviews (MacDougall et al, 1995;Cline and Meyer, 1996;Schütt and Nöthiger, 2000; Sánchez et al, 2005). For other aspects on sex-determining mechanisms in other organisms see revisions by De Loof and Huybrechts (1998), Lalli et al (2003) and Manolakou et al (2006). This revision focuses on sex determination in the somatic component of the animal.…”
Section: The Sex-determining Genetic Cascade Of Drosophila Melanogastermentioning
confidence: 99%
“…Thus it may be that conceptual advances in our understanding of the molecular genetics of testes determination will involve determining how an already identified set of transcription factors interact with each other and with their target genes, rather than identifying additional transcription factors previously not associated with sex determination. Furthermore, as the Affimetrix GeneChip 1 Mouse Genome 430 2.0 array does not survey the non coding RNA transcriptome, addressing the possibility of additional control of mammalian sex determination at the post-transcriptional level must await further technical refinements (Lalli et al, 2003).…”
Section: Global Analysis Of Presumptive Pre-sertolimentioning
confidence: 99%